The relationship between child sexual abuse and female delinquency and crime: a prospective study - Siegel, Jane A. (Journal of research in crime and delinquency, 2003)
Child sexual abuse has been hypothesized to be an especially significant factor in the etiology of girls' delinquency and women's crime. This article reports on a prospective study of 206 women who, in the period from 1973 to 1975, were treated in a hospital emergency room in a major city following a report of sexual abuse. Their subsequent juvenile and adult criminal records were compared to a matched comparison group. Child sexual abuse was a statistically significant predictor of certain types of offenses, but other indicators of familial neglect and abuse were significant factors as well